М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
gravasamp
gravasamp
30.09.2021 14:49 •  Алгебра

Log7(6-x)=0 0сноывние 7 l0g1/4(15-2x)=-3 основание1/4 log11(7-5x)=log11(3+x)+1

👇
Ответ:
stepman228
stepman228
30.09.2021
Log₇(6-x)=0;⇒(6-x)>0;
7⁰=(6-x);⇒1=(6-x);
x=6-1=5;
log₁/₄(15-2x)=-3;⇒log₄⁻¹(15-2x)=-3;
-log₄(15-2x)=-3;
log₄(15-2x)=3;⇒(15-2x)>0;
4³=15-2x;⇒64=15-2x;
2x=-49;
x=-24.5;
log₁₁(7-5x)=log₁₁(3+x)+1;⇒log₁₁(7-5x)=log₁₁(3+x)+log₁₁11;
log₁₁(7-5x)=log₁₁11(3+x);⇒(7-5x)>0;5x< 7;x<7/5; (3+x)>0;3>-x;x<3;
7-5x=11(3+x);⇒7-5x=33+11x;
-5x-11x=33-7;
-16x=26;x=-26/16;x=-1.625;
4,6(43 оценок)
Открыть все ответы
Ответ:
vikakulba
vikakulba
30.09.2021
14(1+√31)+(7 - √31)² = 14 + 14√31  + 7²  - 2*7*√31  + (√31)² =
= 14  + 14√31 + 49  - 14√31  +  31  = (14 + 49 + 31 ) + (14√31 - 14√31)=
= 94

(√43 - 5)² + 10(√43  - 0.2) = (√43)²  - 2*√43 * 5  + 5²  + 10√43 - 2 =
= 43  - 10√43  + 25  + 10√43  - 2 = 66

(11 - √17)(11 +√17) =  11²  - (√17)²  = 121 - 17 = 104

(√2 -√15)² + (√6+√5)²  = (√2)²  - 2*√2*√15 + (√15)²  + (√6)² + 2*√6*√5 +(√5)²=
= 2  - 2√30  + 15  + 6 + 2√30  + 5 = 28

№336.
2√3(√12 + 3√5) - √5(6√3 - √20) = 2√36 + 6√15  - 6√15 +√100=
= 2*6  + 10  = 12 +10 = 22

√6(0,5√24  - 8√11) - 4√11(√99  -2√6) =
= 0,5√144   - 8√66   -  4√1089  +  8√66 =
= 0,5 * 12   -  4*33  = 6  - 132 =  - 126

(√162  - 10√5)√2   + (5 + √10)²  = 
= √324  - 10√10   +  25  + 10√10  + (√10)²  =
= 18  + 25 + 10 = 53

(17  - √21)² - 5√3(4√27   - 6,8√7) =
= 17²  - 2*17*√21  + (√21)²   - 20√81  + 34√21 =
= 289  - 34√21  + 21  - 20*9   + 34√21 =
= 289 + 21  - 180  = 130
4,6(64 оценок)
Ответ:
skyyymbria
skyyymbria
30.09.2021
5y  - ( 7 - 2y) - (7y + 8) = 2y
5y  - 7  + 2y   - 7y  - 8  = 2y
(5y  + 2y  - 7y)  - (7 + 8) = 2y 
- 15  =  2y
2y = - 15
y =  - 15/2
y =  - 7,5

6у(13у-9)  - 13у(6у - 1) = 24 +13
78у²   - 54у  -  78у²  + 13у = 37
(78у² - 78у² ) - (54у-13у) = 37
-41у = 37
у= - ³⁷/₄₁

(2х   - 3)² - (2х + 1)(2х - 5) = 3х - 14
(2х)²  - 2*2х * 3  +  3²  - (4х² - 10х  + 2х  - 5) = 3х  - 14
4х²  - 12х  + 9  - (4х²  - 8х  - 5)   =  3х  - 14
4х²  - 12х  + 9  - 4х²  + 8х  + 5   =  3х  - 14
(4х²  - 4х²)   - (12х - 8х)  + (9 + 5) = 3х  - 14
- 4х  + 14  =  3х  - 14
- 4х   - 3х  = - 14 - 14
- 7х =  - 28
7х = 28
х = 28 : 7
х = 4
4,7(15 оценок)
Новые ответы от MOGZ: Алгебра
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ